The Rise of University Mergers in Europe - Estermann, Thomas; Pruvot, Enora Bennetot (International Higher Education, 2015)
Mergers in the university sector are a growing phenomenon in many European countries. This article explores the rationale and aims behind these processes, underlining that generating economies should not be a primary driver. Costing the process adequately is nevertheless one of the keys to a successful merger, along with a series of other important elements detailed in full in the EUA report dedicated to the issue.